A luminescence‐based chronology for the Harletz loess sequence, Bulgaria. (8th October 2018) - Lomax, Johanna; Fuchs, Markus; Antoine, Pierre; Rousseau, Denis‐Didier; Lagroix, France; Hatté, Christine; Taylor, Samuel N.; Till, Jessica L.; Debret, Maxime; Moine, Olivier; Jordanova, Diana
Abstract : The Harletz loess‐palaeosol sequence is located in northwestern Bulgaria and represents an important link between well‐studied loess sequences in eastern Romania and further sites to the west of the Carpathians (e.g. Serbia and Hungary). The aim of this study was to establish a chronostratigraphy of the deposits, using various methods of luminescence dating, together with basic stratigraphical field observations as well as magnetic properties. Luminescence dating was carried out using the quartz fine grain fraction and a SAR protocol, and the feldspar coarse grain fraction, applying the MET‐pIRIR protocol. Due to underestimation of the quartz fine grain fraction in the lower parts of the sequence, the resulting chronology is mainly based on the feldspar ages, which are derived from the stimulation temperature at 150 °C. A comparison with nearby sequences from Serbia, Hungary and Romania, and interpretations obtained through the stratigraphical and sedimentological signature of the sequence, supports the established chronology. Our data suggest that the prominent palaeosol (soil complex) in the upper quarter of the sequence was formed during MIS 5. It would follow that large parts of the Last Glacial loess overlying this palaeosol were probably eroded, and that the thick loess accumulation underlying this soil complex can be allocated to the penultimate glacial (MIS 6). A prominent MIS 6 tephra, which has been reported from other sequences in the area, is also present at Harletz.